Aspectos clínicos e epidemiológicos da infecção por pseudomonas aeruginosa em pacientes portadores de fibrose cística no Estado do Pará - MARTINS, Valéria de Carvalho (Universidade Federal do Pará, 2013)
Pseudomonas aeruginosa is a gram-negative motile rod; they are important pathogens in neutropenic patients, burn and artificially ventilated patients in Intensive Care Units, where they may cause nosocomial infections. At this condition, the infection seems to be serious and sometimes lethal. However, in Cystic Fibrosis patients the course of infection by P. aeruginosa, has become severe chronic lung infection, because this bacteria produce many toxins and others virulence factors with potential effect on the lungs of this patients that are thought to play a role during establishment of the initial persistent colonization of the Cystic Fibrosis respiratory tract. The most characteristic feature of persistent P. aeruginosa infection is the production of mucoid alginate and the formation of the micro colonies in the lungs of the patients that is the survival strategy of environrnent bacteria. P. aeruginosa growing in alginate biofilms is highly resistant to antibiotics and is usually associated with progressive loss of pulmonary function. This research wants to study Cystic Fibrosis patients chronically colonized by P. aeruginosa who has been taken care on University Hospital João de Barros Barreto, Belém (Pará), in 2003 year, at about epidemiological and clinicalaspects. The sputum of these patients, have been collected by expectoration and swab of throat, to microbiological study realized on microbiology laboratory of this hospital. Thirty two patients with Cystic Fibrosis have been evaluated and divided according microbiological aspect of their sputum in three groups: patients who have never been infected by P. aeruginosa (Gl), patients that have been infected by this bacterial but not colonized (G2), patients chronically colonized by this microorganism. Patients who concern to G3 group have been more serious respiratory complications than patients that belong to the others groups. The pattern mucoid of P. aeruginosa has been significant on patients' sputum of G3. The incident of non- mucoid strains in most patients of groups G2 and G3 seems to be similar. Respiratory symptoms have been important during diagnosis of Cystic Fibrosis. The median age for fibrosis cystic diagnosis was about 7,69 years. Certainly several events contribute to support P. aeruginosa respiratory colonization on Cystic Fibrosis patients of G3, like: low social and economic conditions, lateness diagnosis, malnutrition and pattern Cystic Fibrosis gene mutation.